Screening of analgesic activity of flacourtia jangomes flesh on swiss albino mice. - Akter, Mehenaj (Brac University, 2024)
A project submitted to the School of Pharmacy in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy.